Tuning the tribological performance of plasma-treated hybrid layers of PEEK-GO-DLC. (December 2022) - Awaja, Firas; Guarino, Roberto; Tripathi, Manoj; Fedel, Mariangela; Speranza, Giorgio; Dalton, Alan B.; Pugno, Nicola M.; Nogler, Michael
Abstract: Graphene and graphene oxide (GO)-based coatings are of great interest due to their mechanical, electrical and/or thermal performance that add functionalities to materials employed in many industrial and biomedical applications. Hybrid diamond-like carbon (DLC)/GO coatings on poly ether etherketone (PEEK) devices, e.g. orthopaedic implants, can add multiple functionalities, such as an enhanced bioactivity. In this work, we describe the mechanical stability and tribological behaviour of such coating, comparing it to a DLC-coated bare PEEK. The GO functionalisation of PEEK is realised from a water solution, whereas the DLC coatings are obtained through plasma-enhanced chemical vapour deposition, using various combinations of different precursor gases. We employ atomic force microscopy to investigate the morphology and interfacial adhesion characteristics of the materials. Then, the scratch coefficient of friction of the samples is measured under both constant-load and progressive-load conditions, also in combination with acoustic emission signals. We identify the most effective and promising plasma treatments to ensure stable coating, and discuss the effect of the presence of an intermediate GO layer. Highlights: Hybrid DLC/GO nanocoatings are deposited on PEEK via plasma-enhanced chemical vapour deposition. The objective is to tune the tribological performance (e.g. wear) and mechanical stability of PEEK. The scratch coefficient of friction under constant and progressive load is evaluated. The plasma treatment influences the structure and property of the nanocoatings. The presence of GO as intermediate layer improves the mechanical stability of the surface.